A comparative study for calculating dispersion curves in viscoelastic multi-layered plates. (15th August 2022) - Orta, Adil Han; Kersemans, Mathias; Van Den Abeele, Koen
Abstract: This study examines and critically compares various commonly used models for calculating complex wavenumbers in viscoelastic orthotropic multi-layer materials (e.g. fiber reinforced polymer laminates). Both exact 3D elasticity theory based methods and approximate methods are considered for wave propagation analysis: (i) global matrix method (GMM), (ii) stiffness matrix method (SMM), (iii) hybrid compliance-stiffness matrix method (HCSMM), (iv) semi analytical finite element (SAFE) method, (v) Legendre polynomial method (LPM), and (vi) fifth order shear deformation theory (5-SDT). A detailed mathematical formulation is provided for each of these techniques. The accuracy and the computational efficiency for calculating complex wavenumbers over a wide frequency range are analyzed for both homogenized and multi-layered viscoelastic orthotropic media. This information is helpful to select the proper method to be used in inversion schemes for material characterization. A comparative analysis is also performed on the computed through thickness displacement fields within the solid medium. The different implemented methods have been compiled in a toolbox with a graphical user interface, called "The Dispersion Box", and can be freely downloaded from Orta et al. (2022). Highlights: A benchmark study for dispersion and attenuation behavior of viscoelastic materials GMM, as reference, is compared with SMM, HCSMM, SAFE, LPM and 5-SDT The comparison is performed in terms of accuracy, speed and robustness. A MATLAB toolbox called 'The Dispersion Box' can be downloaded freely